Usability assessment of a HOTS evaluation tool in Pancasila-based Citizenship Education - Agustina, Dewiyana; Sutini, Ai; Abidin, Yunus; Dewi, Dinie Anggraeni; Utami, Nissa Aulia Belistiana (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
The goal of this study is to use the System Usability Scale (SUS) method to see how useful a Higher Order Thinking Skills (HOTS) assessment tool would be in Pancasila Education. Thirty fifth-grade Pancasila Education teachers from primary schools took part in a quantitative descriptive method. We used SUS scores to determine how useful the developed tool was, using established usability standards to do so. The results show that the instrument got an average SUS score of 76.5, which puts it in the "practical" and "good" categories. More research shows that teachers thought the tool was easy to use, understood its instructions, and felt sure they could use it in the classroom. These results show how important it is to test the usability of educational tools, especially those that are meant to help people learn 21st-century skills. The study suggests that practicality testing should be a key part of validating educational tools and that more research should be done on how usable they are in digital and long-term learning settings.